The Opening of ‘The Cares of Winter’ as the Structural Code of The Seasons - Šeferis, Vaidas (Senoji Lietuvos literatūra, 2014)
This paper offers a micro-compositional textual analysis of the opening of ‘The Cares of Winter’, one of the four parts of The Seasons by Kristijonas Donelaitis. The analysis reveals the unique nature of this text and gives an insight into the general features of Donelaitis’ poetics, such as conflicting narrative-temporal structures (circular and linear), the topology of the poetic universe (in which the categories of order and disorder are depicted as the primary ones), and the structural discrepancy between the paradigmatic and syntagmatic levels of the text. The analysis leads to the conclusion that The Seasons should not be considered as an integral and coherent narrative poem, but as a poetical cycle of four independent poems.The micro-compositional analysis of ‘The Cares of Winter’ reveals important features in Donelaitis’ poetics. The deep structure of The Seasons is characterized by the systematic aspects of order and symmetry: each phenomenon depicted in The Seasons has its antipode, while on the syntagmatic plane of the text we observe a contrasting play of their expression. The second principle of the syntagmatic composition of The Seasons is the associative coherence typical in a spoken text. The analysis also highlights the systemic differences of text coherence on the syntagmatic and paradigmatic planes. The ‘disorders’ of the structural symmetry of the text, which enable the introduction of a new subspecies of characters in The Seasons or a consideration of the relationship between linear and cyclic time in the narrative poem, are also significant.
Keywords: -